1996
DOI: 10.1063/1.361352
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the giant magnetoresistance of symmetric and bottom spin valves (invited)

Abstract: We have attempted to optimize the values of the giant magnetoresistance in symmetric spin valves of the type NiO/Co/Cu/Co/Cu/Co/NiO (achieving 23.4%) and in bottom spin valves of the type Co/Cu/Co/NiO (achieving 17.0%), the largest values ever reported for such structures. The key elements in this achievement are improved vacuum conditions and careful attention to the film thicknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…A certain degree of specular scattering was argued to be the origin of high values of GMR in the experiments performed by Egelhoff et al 89,90 on NiO-based symmetric spin valves. A symmetric spin valve 87 contains one free ferromagnetic layer sandwiched between two pinned magnetic layers, separated by nonmagnetic spacer layers, which allows higher magnitudes of GMR to be obtained than in ordinary spin valves.…”
Section: Outer Boundary Dependencementioning
confidence: 95%
See 1 more Smart Citation
“…A certain degree of specular scattering was argued to be the origin of high values of GMR in the experiments performed by Egelhoff et al 89,90 on NiO-based symmetric spin valves. A symmetric spin valve 87 contains one free ferromagnetic layer sandwiched between two pinned magnetic layers, separated by nonmagnetic spacer layers, which allows higher magnitudes of GMR to be obtained than in ordinary spin valves.…”
Section: Outer Boundary Dependencementioning
confidence: 95%
“…Specular scattering of electrons at Co/CoO interfaces was also suggested to be the reason for the enhancement of GMR by up to 17% at room temperature, obtained in bottom spin valves of the type NiO/Co/Cu/Co, in which the top Co layer was slightly oxidized. 91,90 Sugita et al 92 regarded the high magnitude of GMR of 28% obtained in an epitaxially-grown symmetric spin valve with an α- The importance of overlayers deposited at the top outer boundary of the NiO/Co/Cu/Co spin valve was demonstrated by Egelhoff et al 93 They found that the deposition of about 2 monolayers (ML) of Au, Ag, or Cu increases GMR, whereas the deposition of 2ML of Ta, Si, C, or Ni 80 Fe 20 decreases GMR. These results were interpreted by Egelhoff et al as evidence of enhanced specular scattering for the case of Au, Ag, and Cu, but suppressed specular scattering for the case of Ta, Si, C, and Ni 80 Fe 20 at the interface with Co.…”
Section: Outer Boundary Dependencementioning
confidence: 99%
“…Representative and record values for the GMR e!ect both in the CIP and the CPP geometry have been compiled in Table 4. Current e!orts to increase the e!ect in the case of double layers include slight oxidation of the outer surfaces which is believed to lead to smoothening and increase of the electron specular re#ection [25].…”
Section: Giant Magnetoresistance (Gmr)mentioning
confidence: 99%
“…6 In addition, new developments such as the dual spin-valve structures 7 have shown promising results with GMR values of 25%. 4 While the GMR value has continued to increase due to the aforementioned efforts, less attention has been given to the development of other potential device structures with new attributes. In this work, we explore a new type of spin-valve structure that exhibits good field sensitivity and low Barkhausen noise.…”
mentioning
confidence: 99%
“…Intense research efforts on the improvement of spin valves have centered on the enhancement of the GMR effect size, currently about several percent. These efforts have primarily focused on improving sample preparation conditions, 4 adjusting the interfacial scattering between layers, 5 and optimizing post annealing treatments. 6 In addition, new developments such as the dual spin-valve structures 7 have shown promising results with GMR values of 25%.…”
mentioning
confidence: 99%